Pengaruh Model Problem Based Learning dengan Scaffolding Learning Activities terhadap Kemampuan Memecahkan Masalah Siswa - Esti Yuliawanti; Suciati Suciati; Joko Ariyanto (BIO-PEDAGOGI, 2019)
The aim of this research is to know the influence of problem based learning model with scaffolding learning activities toward student’s problem solving skill. This research was a quasi-experiment research. The research was design using pretest-postes with non equivalent group design. The experiment class was used problem based learning model with scaffolding learning activities  while the control class used conventional learning method. The population of this research were all students in X class of SMA Islam 1 Surakarta in academic year 2015/ 2016. Sampling  techniques used cluster random sampling. The data was collected using essay test, multiple choice test of Problem Solving Skill Test (PSST) and observation sheet. The data were analyzed by t-test.Based on the calculation of the t test on the problem solving skill obtained t value 0,000 with the Sig .< 0.05. Problem solving skill mean result from experiment class is 56.12 while control class is 48.29.Based on the research it can be concluded that  problem solving skill problem based learning model with scaffolding learning activities affect student’s problem solving skill.